Senegal's Infrastructure : A Continental Perspective - Briceño-Garmendia, Cecilia M. (World Bank, Washington, DC, 2017)
Between 2000 and 2005 infrastructure made a contribution of 1 percentage point to Senegal's improved per capita growth performance, placing it in the middle of the distribution among West African countries during the period. Raising the country's infrastructure endowment to that of the region's middle-income countries (MICs) could boost annual growth by about 2.7 percentage points. Senegal has made significant progress in some areas of its infrastructure. In the transport sector, road standards are adequate and their quality average. Senegal has also strengthened the road institutional framework with the creation of the Second Generation Road Fund (FERA) and the Road Maintenance Executing Agency. It has also managed to have a toll road concession granted for the Dakar-Diamniadio Toll Highway. The tariffs in the railway sector are internationally competitive, and there has been improvement in the financial viability of ports. After Nigeria, the country stands as an emerging hub and a major player in air transport. Also, Senegal has managed to introduce private participation in electricity generation, and the unbundling of the electricity sector is under way even as the country actively participates in the regional power market. The country is on track to meet the Millennium Development Goals (MDGs) in improved water. In the information and communication technology (ICT) sector there has been an impressive expansion of the mobile and Internet markets. Senegal already spends around $911 million per year on infrastructure, equivalent to about 11 percent of its gross domestic product (GDP). Almost $312 million a year is lost to inefficiencies of various kinds, associated mainly with under-pricing in the power and water sectors, poor financial management of utilities, and inefficient allocation of resources across sectors. If Senegal could raise tariffs to cost-recovery levels and reduce operational inefficiencies in line with reasonable developing-country benchmarks, it could substantially boost its infrastructure sector.